Subject Embedding, Relationship Interaction, and Resource Integration: The Value Co-Creation Mechanism in Rural Communities - Wu, Yingqiu; Xu, Lu; Lin, Jianwu; Ghani, Muhammad Imran (Systems (Basel), 2023)
Globalization and urbanization have reshaped the way that service ecosystem subjects interact with each other in rural communities, providing conditions and possibilities for realizing value co-creation in rural communities. Therefore, this study selected rural communities in Guiyang City, China, as research subjects and explored the value co-creation mechanism in rural communities from the perspective of service ecosystems. The authors construct a theoretical framework encompassing “value co-creation conditions, value co-creation processes, and value co-creation results”. The study found that the core mechanism in the process of value co-creation is “subject embedding, relationship interaction, and resource integration”. At the macro level, resource sharing is achieved through complex and heterogeneous interactions among multiple subjects, under the influence of institutions, policies, and cultures. At the meso level, organizations complement each other’s resources through the cooperation and empowerment of other actors horizontally, under the influence of structure, function, and rules. At the micro level, individuals optimize resources through cooperative and empowering interactions, under the influence of motivations and value preferences. Finally, the integration of individual, organizational, and overall values constitutes public values, under the joint cross-level action of institutional and cultural elements. This study provides a new theoretical perspective for exploring the value co-creation mechanism in rural communities and provides important practical insights for promoting the sustainable development of rural communities.